A fully coupled numerical model for deposit formation from evaporating urea-water drops. (October 2020) - Bender, Achim; Stephan, Peter; Gambaryan-Roisman, Tatiana
Highlights: Novel numerical model for deposit formation from evaporating urea-water drops. Detailed analysis of heat and mass transfer in evaporating drop, deposit, and gas. Deposit shape affects contact line temperature and evaporation rate. Impact of temperature, composition, and radius on deposit formation quantified. Deduction of characteristic time scale and of a correlation for start of deposition. Graphical abstract: Abstract: Evaporation and deposit formation of a pinned urea-water drop on an initially smooth surface is modeled. Water evaporates from the two-component drop into the surrounding gas phase. This leads to an increase of the urea concentration inside the drop. At the three-phase contact line, high evaporation rates lead to a maximum of the urea concentration. As a result, heterogeneous nucleation and growth of urea crystals takes place in the vicinity of the three-phase contact line. The model resolves the deformation of the liquid–gas interface using a moving mesh and an arbitrary Lagrangian–Eulerian method (ALE). The deposit shape and the influence of the deposit on the transport processes in the drop are accounted for. The drop evaporation agrees quantitatively with a correlation, and the deposit shape matches qualitatively with experimental investigations from the literature. A parametric study reveals that the wall temperature, initial drop composition, and drop radius influence the deposit formation process. The time instant of deposit nucleation and the deposit shape depend on the choice of these parameters. A characteristic time scale is identified and a correlation to predict the beginning of deposit formation is derived. Once the deposit formation has started, the deposit growth rate increases with time.